PEMETAAN BISNIS KULINER DI KOTA MALANG - Agatha Calista (Parsimonia - Jurnal Ekonomi dan Bisnis, 2017)
The rise of the culinary in Indonesia has progressed very fast. The unfortunate be simultaneous city change at industry and services including tourism and education for the area around it. A culinary business is one of the industry which is growth in the unfortunate that rises very rapidly. Culinary business is an industry advocates property hotel, shopping places, and road infrastructure. This study attempts to culinary business mapping based on attributes and classification restaurant which is divided into the sub districts in the Malang City and expected to provide information for government about the progress of culinary business based on attributes and classification in their areas and contributing to the culinary businesses that opens or even develop business in seeing the availability business opportunities, determine markets, positioning, and marketing strategy that are suitable for all segments there. Variables that used in this research is an attribute (the atmosphere, location, facilities, service, product) and classification of the culinary business. Data analysis technique that used in this research is mapping techniques culinary business based on 5 (five) subdistricts in the town of Malang. The result showed that the majority of culinary business who were adequate and complete located in Klojen Subdisctrict and most culinary business who were inadequate and less full located in Sukun Subdistrict.